2021
DOI: 10.1101/2021.07.26.21261119
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety and efficacy of COVID-19 hyperimmune globulin (HIG) solution in the treatment of active COVID-19 infection- Findings from a Prospective, Randomized, Controlled, Multi-Centric Trial

Abstract: Background COVID-19 hyper-immune globulin (HIG) solution is a human plasma-derived, highly-purified, concentrated, virus-inactivated preparation of neutralizing antibodies (NAbs) against COVID-19. Methods This was a randomized, two-arm, controlled, multi-center trial to evaluate the efficacy and safety of COVID-19 HIG in patients who were hospitalized with moderate-severe COVID-19 infection. Results A total of 60 patients were randomized (30 in each arm). Overall, COVID-19 HIG was well-tolerated without any se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…For patients who fail to seroconvert, the ongoing management is likely to remain a challenge and they will almost certainly rely on passive immunity. In some settings, hyperimmune COVID‐19 immunoglobulin 40 is available but supply is likely to remain limited. Immunoglobulin replacement therapies may soon have anti‐S antibodies detectable; however, the level of antibody and whether it confers any protective activity will be difficult to establish.…”
Section: Discussionmentioning
confidence: 99%
“…For patients who fail to seroconvert, the ongoing management is likely to remain a challenge and they will almost certainly rely on passive immunity. In some settings, hyperimmune COVID‐19 immunoglobulin 40 is available but supply is likely to remain limited. Immunoglobulin replacement therapies may soon have anti‐S antibodies detectable; however, the level of antibody and whether it confers any protective activity will be difficult to establish.…”
Section: Discussionmentioning
confidence: 99%
“…PRISMA flow diagram can be seen on Figure 1 . A total of 6 studies were excluded for not reporting on an adequate control group, 21 , 22 , 23 , 24 , 25 , 26 while 3 studies reported on convalescent plasma or hyperimmune anti‐SARS‐CoV‐2 serum 27 , 28 , 29 and some assessed studies were reviews, commentaries or publications that did not report any new data.…”
Section: Resultsmentioning
confidence: 99%
“…One phase I/II trial randomised 50 hospitalised COVID-19 patients to COVIG or standard of care and demonstrated a lower mortality in the COVIG arm (25% in COVIG arm versus 60% in control group), however, this benefit could not be confirmed in two phase III trials. [17][18][19] Highly potent virus neutralizing monoclonal or combined monoclonal antibodies yield supraphysiological levels of neutralizing antibodies unachievable with plasma-derived products. The landmark trial by the UK RECOVERY group evaluating treatment with a combination of casirivimab and imdevimab in hospitalised patients showed reduced mortality, but only in the predefined subgroup of seronegative patients.…”
Section: Introductionmentioning
confidence: 99%